Sustainable microgrid design considering blockchain technology for real-time price-based demand response programs - Tsao, Yu-Chung; Thanh, Vo-Van; Wu, Qiuwei (International journal of electrical power & energy systems, 2021)
•This study addresses the sustainable mircogrids design problem under competition.•Leveraging blockchain technology to provide the demand response programs.•Three sustainable objectives (economy, environment, and society) are considered.•A robust fuzzy multi-objective optimization approach is proposed.•The proposed model and solution approach are then applied to a case study in Vietnam. In recent years, rapidly increasing electric power demand and organizational concerns regarding social and environmental issues have resulted in significant attention being given to microgrids. However, sustainable microgrids that simultaneously address economic benefits and environmental and social issues have not been broadly explored by researches. This study addresses the sustainable microgrid design problem by leveraging blockchain technology to provide the real time-based demand response programs. Three sustainable objectives (economy, environment, and society) are formulated by a multi-objective mixed integer-linear programming model. A robust fuzzy multi-objective optimization approach is proposed to determine the optimal number, location, and capacity of renewable distributed generation units as well as the equilibrium supply and dynamic pricing decisions under uncertain demand, capacity, and economic, environmental, and social parameters. The proposed model and solution approach are then applied to a case study in Vietnam. We find that blockchain technology-based sustainable microgrid can result in a 1.68% and 2.61% increase of profitability and consumer satisfaction, respectively, and a 0.97% reduction of environmental impacts.